Magnus Stevns - Riisager, Vagn (Grundtvig-Studier, 1949)
Magnus Stevns: In Memoriam. By Vagn Riisager. Magnus Stevns, the student of Grundtvig, who died on March 30, 1949, was born in 1900 and was the son of the Headmaster of Kvissel High-School. As a young man he worked in agriculture and, at intervals, was a pupil at Askov and Støvring High-Schools; afterwards he took the University entrance examination and studied at Copenhagen University, where he was especially influenced by Valdemar Vedel. He took his M. A. Degree in the History of Literature in 1930, and in 1934 became cand. mag.; after this he was a much-valued teacher at the Danish Teachers’ Training College. Stevns was always a good disciple of the spirit of the Danish Folk High-School ; most of his written works deal with folk-songs and Grundtvig’s hymns; his essays, though based on conscientious research on special subjects, are always related to a central idea. In particular, his accounts of Grundtvig’s spiritual characteristics, theology and hymn-writing are of such importance that a collected edition of them ought to be published.